Factors Correlating to Mothers’ Knowledge on Toddler’s Nutrition Need - Chasanah, Nur; Supriani, Anik; Widiyawati, Rina (Jurnal Midpro, 2022)
Childhood is the early phase of life and a very fast growth and development phase. Good nutrition intake plays an important part in achieving optimum body growth, including brain growth as well highly determining an individual’s intelligence. Toddlers are more interested in environment and improving their motor skill than in food; therefore, the food served should be always varying. The objective of research is to find out the factors correlating to mothers’ knowledge on nutrition need in toddlers. The result of observation conducted by the author in Cermee Village, Cermee Sub District, Bondowoso found many mothers with toddlers (1-3 year children) have poor knowledge on the nutrition need in 1-3 year old children. The method used was quantitative one, with descriptive correlational design and cross-sectional approach and exhaustive sampling technique taking 34 respondents being the sample. The result of univariate analysis shows that 67.7% of respondents have poor knowledge on toddler’s nutrition need and factors correlating to mothers’ knowledge on toddler nutrition are occupation and information source with substantially different proportion (>10%). Meanwhile, education and age factors have very small proportion difference.  Keywords: Knowledge, Nutrition Need, Toddler